Satisfacción de los beneficiarios del “Proyecto de adulto mayor modalidad de espacios activos de socialización y encuentro con alimentación”, implementado por el GAD Municipal de Yantzaza, año 2024. - Puchaicela Avila, Carmen Geovanna (2025)
The present research work entitled: “Satisfaction of the beneficiaries of the ‘Project for older adults modality of active spaces for socialization and meeting with food’, implemented by the GAD Municipal de Yantzaza, year 2024”, had as general objective to evaluate the satisfaction of the public policy of the gerontological care centers, for the achievement of this purpose two objectives have been raised: first, to identify the needs of the beneficiary older adults; and second to determine the satisfaction generated in the beneficiaries of the project. For this purpose, it is taken into account that the level of satisfaction goes beyond verifying the fulfillment of the project's objectives; this research verifies whether the fundamental needs of the population were satisfied. For this, the research had a non-experimental design, since no variables were manipulated; the approach used was of a mixed nature, since the instruments used for data collection were surveys that provided quantitative and qualitative data; the sample included 150 older adult beneficiaries of the project. The results indicated that the fundamental needs in most of the older adults are: “socialization and coexistence”, “activities” and “food”; they also showed a total satisfaction of 33. 10 points, which when divided among the 24 sub- variables evaluated gave an average of 1.38 points per sub-variable, this average reflects the overall satisfaction level of the older adults which implies that perceptions exceeded expectations by a percentage of 17%, however this is relatively low; this suggests that, although some needs of the older adults have been satisfied, there are areas in which the project could be improved.